Further Validation of the Crohn’s and Ulcerative Colitis Questionnaire-32 (CUCQ-32) to Measure the Quality of Life in Patients Treated with Biologics Therapy - Laith Alrubaiy (Clinics and Practice, 2022)
Background: Crohn’s and Ulcerative Colitis Questionnaire-32 (CUCQ-32) is a validated questionnaire to measure the quality of life (QoL) in Inflammatory Bowel Disease (IBD). However, it does not have stoma-specific questions and can be lengthy. This study aimed to validate a subset of the CUCQ-32 that would be suitable for patients with a stoma. Methods: Baseline data were collected from a cohort of patients with acute ulcerative colitis who were participating in the CONSTRUCT multicentre clinical trial. A subset of the CUCQ-32 questions was selected by stepwise regression. Further validation was examined using data from the UK IBD biological therapies audit. Construct validity was carried out using the EuroQol 5 dimensions (EQ5D) questionnaire, Simple Clinical Colitis Activity Index (SCCAI), and the Harvey–Bradshaw Index (HBI). Results: Using the data from 124 patients, a short-version questionnaire (CUCQ-12) was developed. Data from 484 patients with IBD (382 patients with Crohn’s disease, 76 patients with ulcerative colitis, and 26 patients with IBD-Unclassified) and 61 patients with stoma provided further validation of the CUCQ-12. A literature review and an expert focus group identified supplementary stoma-specific questions for the CUCQ-12+. The CUCQ-12+ demonstrated excellent internal consistency (Cronbach’s α = 0.86); established effective reproducibility (intra-class correlation coefficient = 0.74); correlated well with the EQ5D (r= −0.48), HBI (r = 0.45), and SCCAI (r = 0.43); and represented good responsiveness statistics (>0.5). Conclusions: CUCQ-12+ is a valid and reliable QoL measure used for all patients with IBD in clinical practice, including patients with a stoma.